Homo Fidei: A Critical Understanding of Faith in the Writings of Wilfred Cantwell Smith and Its Implications for the Study of Religion - Graham, Thomas (Implicit religion, 2007)
The article reviews the book "Homo Fidei: A Critical Understanding of Faith in the Writings of Wilfred Cantwell Smith and Its Implications for the Study of Religion," Volume 24, by Kuk-Won Bae.